Effect of ash in paper sludge on enzymatic hydrolysis. (October 2022) - Park, Hyeonji; Cruz, David; Tiller, Phoenix; Johnson, David K.; Mittal, Ashutosh; Jameel, Hasan; Venditti, Richard; Park, Sunkyu
Abstract: The valorization of paper sludge is a high-potential process to develop renewable fuels and chemicals, which can be integrated with pulp and paper mills. Calcium carbonate is the main ash component in sludge, which plays a role in buffering pH and potentially lowering the conversion during enzymatic hydrolysis. Therefore, it is important to investigate the effect of ash on sugar yields and examine pH change to introduce efficient and economical enzymatic hydrolysis of sludge. Carbohydrate conversion was enhanced when the ash was removed by fractionation. On the other hand, the highest sugar recovery was obtained when the sludge contained 20% ash content. The pH change during enzymatic hydrolysis was influenced by ash and explained why sludge-derived hydrolysate showed lower carbohydrate conversion. Therefore, a high shear process with the increased acid amount is suggested to prohibit the negative effect of ash and enhance the accessibility of cellulase to fibers. This study highlights the feasibility of using wet waste streams generated by the paper industry. Highlights: Enhanced carbohydrate conversion of sludge containing low ash after fractionation. Enhanced carbohydrate conversion by lowering the starting pH environment. Observed pH change during hydrolysis to understand the adverse effect of ash. Obtained maximum sugar recovery when paper sludge contained 20% ash. Provided the efficiency of enzymatic hydrolysis depending on the ash content.